THE IMPACT OF PERCEIVED BRAND INTERACTIVITY, SOCIAL MEDIA MARKETING, AND HALAL LABELING ON PURCHASING DECISIONS: THE MEDIATING ROLE OF TRUST IN TIKTOK SHOP - Dyah Arfiyanti (Journal of Management and Islamic Finance, 2025)
This study examines the influence of perceived brand interactivity, social media marketing, and halal labeling on purchasing decisions, with trust as a mediating variable. A total of 96 Hanasui cosmetic users in Salatiga City who had experience with the TikTok platform were selected through purposive sampling. Data analysis involved instrument testing, classical assumption testing, and path analysis. The results show that perceived brand interactivity has no significant effect on either trust or purchasing decisions. In contrast, social media marketing and halal labeling significantly and positively affect both trust and purchasing decisions. Furthermore, trust plays a pivotal role, not only directly influencing purchasing decisions but also mediating the effects of perceived brand interactivity, social media marketing, and halal labeling. These findings highlight that trust strengthens the effectiveness of social media marketing and halal labeling in shaping consumer behavior, while brand interactivity alone is insufficient to drive purchasing decisions. Among the variables tested, social media marketing and halal labeling emerged as the strongest predictors of purchasing decisions for Hanasui products on TikTok. Overall, this study underscores the strategic importance of building consumer trust through social media marketing and halal labeling in Indonesia’s digital marketplace.